Istrobeneščina med pripadniki italijanske narodne manjšine v slovenski Istri - Todorović, Suzana (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2021)
During the dialectological research carried out in recent years in some Istrian-Venetian localities (towns), we have learned from conversations with dialect speakers that the Istrian-Venetian dialect is most probably the language of communication of most members of the Italian national community in the coastal part of Slovene Istria. In order to get a more accurate and detailed insight into the use of the Istrian-Venetian dialect spoken by Italians in formal and informal speech situations, we conducted a quantitative survey with 232 randomly selected respondents and a qualitative survey with 50 interviews. The respondents answered various multiple-choice questions about the languages they use in their daily lives. Research has shown that the Istrian-Venetian dialect is the predominant idiom among members of the Italian national community in Slovene Istria, except when communicating with non-Italian interlocutors and in official institutions where, despite the right to use their language, i.e., Italian, the predominant language is Slovene.
Keywords: Istrian-Venetian dialect; istrskobeneško narečje; Italian ethnic group; Italian language; italijanska narodna skupnost; italijanski jezik; language of communication; narodne manjšine; national minorities; Slovene Istria; Slovene language; slovenska Istra; slovenski jezik; sporazumevalni jezik